Treatment of domestic wastewater by vertical flow constructed wetland planted with umbrella sedge and Vetiver grass - Kantawanichkul S. (2014)
The aim of this study was to investigate the efficiency of wastewater treatment by vertical flow constructed wetland systems under different hydraulic loading rates (HLR). The comparison of two types of plants, Cyperus alternifolius (Umbrella sedge) and Vetiveria zizanioides (Vetiver grass), was also conducted. In this study, six circular concrete tanks (diameter 0.8 m) were filled with fine sand and gravel to the depth of 1.23 m. Three tanks were planted with Umbrella sedge and the other three tanks were planted with Vetiver grass. Settled domestic wastewater from Chiang Mai University (chemical oxygen demand (COD), NH4 +-N and suspended solids (SS) of 127.1, 27.4 and 29.5 mg/L on average, respectively) was intermittently applied for 45 min and rested for 3 h 15 min. The HLR of each tank was controlled at 20, 29 and 40 cm/d. It was found that the removal efficiency of the Umbrella sedge systems was higher than the Vetiver grass systems for every parameter, and the lowest HLR provided the maximum treatment efficiency. The removal efficiency of COD and nitrogen in terms of total Kjeldahl nitrogen (TKN) was 76 and 65% at 20 cm/d HLR for Umbrella sedge compared to only 67 and 56% for Vetiver grass. Nitrogen accumulation in plant biomass was also higher in Umbrella sedge than in Vetiver grass in every HLR. Umbrella sedge was thus proved to be a suitable constructed wetland plant in tropical climates. © IWA Publishing 2013.